Zarządzanie aktywami i pasywami banku spółdzielczego a ryzyko stopy procentowej - Kowalski, Olaf; Różyński, Jerzy (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2011)
The first issue raised in the study is the assessment of interest rate risk, evidenced trough interaction between market rates changes and net interest income of the bank. Following subsections of the article refers to maturity mismatch risk, basis risk and client’s option risk. Next issue addressed is the management of assets and liabilities of cooperative bank in reference to interest rate risk. Authors focused here on assets and liabilities management rules in reference to predicted formation of market rates. Further risks were also indicated, which from authors point of view are critical for comprehensive representation of studied issues